Cluster Country Program Evaluation on Small States : Mauritius Country Case Study, Enhancing Competitiveness and Private Sector Development - Charlier, Florence (World Bank, Washington, DC, 2016)
After nearly two decades of strong economic growth, in 2005 the economy was in difficulties. The loss of trade preferences in textiles in 2005, the anticipation of prospective reform to the European Union’s sugar protocol for 2006-10, and higher international oil prices had contributed to a slow-down in growth, rising unemployment and widening fiscal and current account deficits. A new government was elected in 2005 which implemented a series of bold economic reforms (such as the elimination of the export processing zone (EPZ) regime, a progressive liberalization of the foreign trade and investment regime and simplification of labor laws) to redress the macro-economic imbalances and enhance competitiveness to facilitate efficient restructuring of the economy. This was achieved in large measure. Good policies also allowed the government to deal effectively with the global financial crisis of 2008. Following elections in 2010, a new (and fragile) coalition government was elected which emphasized fiscal stimulus and the pace of reforms slowed. Following a period of political instability, a new government was elected in 2014 with an overwhelming majority. However, as fiscal pressures mount, a sense of policy drift continues, threatening the gains achieved in recent years. The World Bank Group supported the government’s reform efforts throughout the evaluation period. Support was provided largely in the form of development policy loans (DPLs), complemented by analytic work and technical assistance (TA) for capacity building in various parts of the government. The World Bank’s strategy was aligned with the government’s priorities during 2005-10, but it failed to adapt when the appetite for reforms waned after a new coalition government took office following elections in 2010. The World Bank’s strategy was flexible and the program underwent significant changes to respond to changing government priorities and unfavorable external conditions. The World Bank’s program addressed the twin challenges of building resilience (macro-economic and social) and enhancing competitiveness that are common to other small states. Perhaps the World Bank could have been more selective in its areas of interventions.